Characteristics, presentation and outcomes of music festival patrons with stimulant drug‐induced serotonin toxicity. (15th April 2021) - Miles, Lachlan F; Austin, Kristy; Eade, Alan; Anderson, David; Graudins, Andis; McGain, Forbes; Maplesden, Jacqueline; Greene, Shaun; Rotella, Joe‐Anthony; Dutch, Martin
Abstract: Objective: A large number of stimulant drug‐associated deaths at music festivals in Australia were reported during the southern hemisphere summer of 2018–2019. This led to the prehospital deployment of healthcare professional‐led critical care response teams. We aimed to describe the characteristics, clinical presentation, management and outcomes of music festival patrons with stimulant drug‐induced serotonin toxicity managed using this model during the study period. Methods: We performed a retrospective observational study of patients presenting with stimulant drug‐induced serotonin toxicity and/or drug‐induced hyperthermia who presented between December 2017 and December 2019. Comprehensive follow‐up data were collected for those patients who required hospital admission. Data included demographics, clinical features, management and disposition, hospital outcomes and laboratory data, stratified by severity of presentation. Results: Forty‐seven patients were included. Median age was 21.9 years (interquartile range 19.6–22.2). 3, 4‐Methylenedioxymetamphetamine was the most frequently reported agent ingested (32/47). After stratification, 13 of 47 patients were classified as mild, 20 of 47 as moderate and 14 of 47 as severe. Median presenting temperature in this latter cohort was 41.1°C (40.5–42.0°C). All severely ill patients required intensive care unit admission, with a median hospital stay of 4.63 days (interquartile range 2.08–8.36). End‐organ complications were reported in 11 of 14 patients. No mortalities were reported. All patients (13/13) from the mild cohort and 15 of 20 patients from the moderate cohort were treated and discharged on‐site. Conclusions: Severe illness was associated with a high incidence of end‐organ impairment. A high proportion of patients without severe disease were able to be successfully managed at the event without transport to hospital. No deaths are reported in this series. Abstract : We have described the clinical presentation and outcomes of a cohort of 47 music festival patrons with stimulant drug‐induced serotonin toxicity managed by a prehospital critical care team. In the group of patients presenting with mild or moderate illness, the vast majority of patients were able to be managed successfully on site without recourse to hospital transport. In the group of patients with severe illness (all of whom required hospital transport), zero deaths were recorded despite very high temperatures on presentation. Notwithstanding the early provision of critical care, end‐organ impairment in this sub‐group was high.